Foliose Ulva Species Show Considerable Inter‐Specific Genetic Diversity, Low Intra‐Specific Genetic Variation, and the Rare Occurrence of Inter‐Specific Hybrids in the Wild. Issue 1 (24th November 2020) - Fort, Antoine; McHale, Marcus; Cascella, Kevin; Potin, Philippe; Usadel, Björn; Guiry, Michael D.; Sulpice, Ronan
Abstract : Foliose Ulva spp. have become increasingly important worldwide for their environmental and financial impacts. A large number of such Ulva species have rapid reproduction and proliferation habits, which explains why they are responsible for Ulva blooms, known as "green tides", having dramatic negative effects on coastal ecosystems, but also making them attractive for aquaculture applications. Despite the increasing interest in the genus Ulva, particularly on the larger foliose species for aquaculture, their inter‐ and intra‐specific genetic diversity is still poorly described. We compared the cytoplasmic genome (chloroplast and mitochondrion) of 110 strains of large distromatic foliose Ulva from Ireland, Brittany (France), the Netherlands and Portugal. We found six different species, with high levels of inter‐specific genetic diversity, despite highly similar or overlapping morphologies. Genetic variation was as high as 82 SNPs/kb between Ulva pseudorotundata and U . laetevirens, indicating considerable genetic diversity. On the other hand, intra‐specific genetic diversity was relatively low, with only 36 variant sites (0.03 SNPs/kb) in the mitochondrial genome of the 29 Ulva rigida individuals found in this study, despite different geographical origins. The use of next‐generation sequencing allowed for the detection of a single inter‐species hybrid between two genetically closely related species, U . laetevirens, and U . rigida, among the 110 strains analyzed in this study. Altogether, this study represents an important advance in our understanding of Ulva biology and provides genetic information for genomic selection of large foliose strains in aquaculture.